Regional to tertiary inter-hospital transfer versus in-house percutaneous coronary intervention in acute coronary syndrome. - Delara Javat; Clare Heal; Jennifer Banks; Stefan Buchholz; Zhihua Zhang (PLoS ONE)
Rationale To address the inaccessibility of interventional cardiac services in North Queensland a new cardiac catheterisation laboratory (CCL) was established in Mackay Base Hospital (MBH) in February 2014. Objective To determine whether the provision of in-house angiography and/or percutaneous coronary intervention (PCI) 1) minimises treatment delays 2) further reduces the risk of mortality, recurrent myocardial infarction (MI) and recurrent ischaemia 3) improves patient satisfaction and 4) minimises cost expenditure compared with inter-hospital transfer for patients with acute coronary syndrome (ACS). Methods We compared ACS patients who were transferred to tertiary centres from July 2012 to June 2013 with those who received in-house angiography and/or PCI from February 2015 to January 2016. The primary outcome was the composite of all-cause mortality, recurrent myocardial infarction (MI) or recurrent ischaemia at six months. Pre-specified secondary outcomes were the composite of all-cause mortality, recurrent MI or recurrent ischaemia at one month, a summated patient satisfaction score and the proportional cost savings generated between 2015 and 2016. Results We included consecutive samples of 203 patients from July 2012 to June 2013 and 229 patients from February 2015 to January 2016. There was a reduction in the median time to treatment of 3.2 days and a reduction in the median length of stay of four days amongst all ACS patients receiving in-house angiography and/or PCI. The primary outcome occurred in 14 (6.9%) patients in the 2012 to 2013 group, as compared with 18 (7.9%) patients in the 2015 to 2016 group (OR = 0.71, 95% CI 0.24-2.1, P = 0.54). The secondary outcome at one month occurred in four (2.0%) patients in the 2012 to 2013 group, as compared with three (1.3%) patients in the 2015 to 2016 group (OR = 1.2, 95% CI 0.11-13.1, P = 0.87). There was a statistically significant improvement in the summated patient satisfaction score amongst patients who received in-house angiography and/or PCI (U = 1918, P <0.05 two tailed). A calculation of estimated cost savings showed a reduction in proportional cost of $14 481 (51%) per ACS patient receiving in house angiography and/or PCI between 2015 and 2016. Conclusion This study suggests that the provision of regional in-house angiography and/or PCI for the treatment of ACS minimises delays to invasive treatment by 3.2 days, minimises the median length of stay by four days, significantly improves patient satisfaction and reduces proportional treatment costs by $14 481 (51%) per patient. Currently, however, it appears that that in-house treatment does not further reduce the risk of mortality, recurrent MI and recurrent ischaemia at one and six months.